The Contribution of Volunteering to Volunteers’ Life: The Case of Volunteering Beneficiaries Turned Volunteers - Ben Yair, Yitzhak (International journal of offender therapy and comparative criminology, 2025)
This study addresses the process experienced by youth who started out as volunteering beneficiaries in treatment settings and became volunteers for at-risk youth themselves. Using the phenomenological approach, the study included 10 Israeli interviewees aged 20 to 30 who were regular volunteers. The findings suggested three themes related to the process experienced by the volunteers: (1) perceived altruism—the altruism attributed to the volunteers who had benefited the participants as youths; (2) the identity transformation from beneficiary to benefactor; and (3) acquired altruism—the acquisition of that trait by the participants. Applying the principles of positive criminology, this study shows how attributing altruism to the behavior of the volunteer can serve as fertile ground for acquiring altruism oneself, in a process that eventually results in volunteering for the benefit of others.